2020
DOI: 10.3390/en13123097
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Assessment of the Use of Syngas Generated from Biomass to Feed an Internal Combustion Engine

Abstract: The focus of this study is to provide a comparative techno-economic analysis concerning the deployment of small-scale gasification systems in dealing with various fuels from two countries, Portugal and Brazil, for electricity generation in a 15 kWe downdraft gasifier. To quantify this, a mathematical model was implemented and validated against experimental runs gathered from the downdraft reactor. Further, a spreadsheet economic model was developed combining the net present value (NPV), internal rate of return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 37 publications
1
13
1
Order By: Relevance
“…Ngan et al [12] formulated a Monte Carlo simulation model to evaluate the financial profitability as well as the impact of various action plans as an attempt to decrease the supply chain risks. Copa et al [40] also evaluated the economic viability of gasification of four types of biomass (i.e., municipal solid waste from Portugal and Brazil, acacia, and eucalyptus) using the Monte Carlo simulation model and concluded that acacia and eucalyptus have a higher risk of investment losses. One of the reasons is the higher acquisition cost for acacia and eucalyptus.…”
Section: Techno-economic Evaluation Models With Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ngan et al [12] formulated a Monte Carlo simulation model to evaluate the financial profitability as well as the impact of various action plans as an attempt to decrease the supply chain risks. Copa et al [40] also evaluated the economic viability of gasification of four types of biomass (i.e., municipal solid waste from Portugal and Brazil, acacia, and eucalyptus) using the Monte Carlo simulation model and concluded that acacia and eucalyptus have a higher risk of investment losses. One of the reasons is the higher acquisition cost for acacia and eucalyptus.…”
Section: Techno-economic Evaluation Models With Optimizationmentioning
confidence: 99%
“…Referring back to Table 1, a few published studies had also utilized Monte Carlo as their evaluation approach. Copa et al [40] had utilized Monte Carlo simulation for risk evaluation in their study of biomass gasification process combined with electricity generation. In this work, all the uncertainties (i.e., discount rate, capital investment, selling price of electricity, operating and maintenance cost, and costs of fuel) are modelled by presuming a ± 30 % manually.…”
Section: Monte Carlo Analysis For Economic Evaluationmentioning
confidence: 99%
“…Several studies tried to evaluate the economic profitability of biomass gasification CHP plants [89][90][91][92][93][94]. Colantoni et al [89] used Montecarlo simulation to evaluate important economic indicators, like Net Present Value (NPV), Internal Rate of Return (IRR) and Payback Time (PBT), of three different gasification CHP power plants (13.6 kW, 136 kW, and 1.9 MW nominal electrical capacity).…”
Section: Cost Efficiencymentioning
confidence: 99%
“…Copa et al [94] presented a comparative techno-economic analysis concerning the deployment of small-scale gasification systems in dealing with various fuels from two countries, Portugal and Brazil, for electricity generation in a 15 kWel downdraft gasifier. The viability of the projects was predicted for an NPV set between 18.99 to 31.65 k€, an IRR between 16.88 to 20.09% and a PBP between 8.67 to 12.61 years.…”
Section: Cost Efficiencymentioning
confidence: 99%
“…In terms of power generation, Internal Combustion Engines-Generators (ICEGs) play a significant role in developing countries [6] due to their lower cost, larger availability and better fuel flexibility [7] when compared to gas turbines [8]. In Brazil, gas engines have been the preferred technology for landfill gas utilization in WtE projects.…”
Section: Introductionmentioning
confidence: 99%